Generalizing Fisher's "reproductive value": overlapping and nonoverlapping generations with competing genotypes. - Samuelson, P A (1978)
How to go beyond Fisher's 1930 linear eigenvector definition of reproductive value has been established for dilute systems whose dynamic relations are first-degree-homogeneous functions so that intensive ratios are scale-free. Here such an extension is applied to standard mendelian models. It is shown that, aside from singular cases like that of the Hardy-Weinberg razor's-edge labile equilibrium, such general systems are irreducibly nonlinear and admit of reproductive value functions that are calculable only in an infinite number of steps.